Antifungal activity of five plant-extracted essential oils against anthracnose in papaya fruit. Issue 1 (2nd January 2018) - Sarkhosh, A.; Schaffer, B.; Vargas, A. I.; Palmateer, A. J.; Lopez, P.; Soleymani, A.; Farzaneh, M.
Abstract: Inhibitory effects of five different plant essential oils were assessed against papaya fruit decay caused by anthracnose. Essential oils were extracted from savory, thyme, cinnamon, mint, and lavender plants and chemical components of each oil were identified by GC-mass spectroscopy. The polymerase chain reaction (PCR) method using the internal transcribed spacer (ITS) primer confirmed the identity of the Colletotrichum gloeosporioides isolate. Then different concentrations of each oil were tested in vitro and in vivo . The in vitro results revealed a 100% reduction of mycelium growth for savory and thyme essential oils. In the in vivo experiment, savory and thyme oils at 2000 μL L −1 caused a 59.26 and 58.40% reduction in lesion diameter and a 64.07 and 54.82% of fruit decay, respectively. Application of savory or thyme oil resulted greater maintenance of fruit firmness than the application of the other essential oils after fruit were inoculated with the anthracnose fungus. Savory oil with the main chemical compound carvacrol (71.2%), and thyme oil with the main chemical constituent thymol (73.3%) were the most effective of the oils tested at controlling anthracnose in vitro and in vivo . The half maximal effective concentration (EC50 ) of savory oil was the lowest among the extracted oils tested, resulting in EC50  = 58.42 μL L −1 for the in vitro test and EC50  = 1507.19 μL L −1 for the in vivo experiment. This study showed that savory oil is effective as a natural fungicide for controlling anthracnose decay and prolonging the storage life of papaya fruit.